Efficiency of Erbium-Doped Yttrium Aluminum Garnet Laser in Debonding Cemented Glass Fiber Posts: an in vitro Study - Amir Hossein Zamanian; Seyed Mohammad Reza Hakimaneh; Seyed Masoud Mojahedi; Farnaz Taghavi Damghani; Fatemesadat Shayegh; Sayed Shojaedin Shayegh (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: The efficacy of erbium-doped yttrium aluminum garnet (Er: YAG) laser on the debonding properties of certain post materials has remained largely unexplored. Purpose: This study aimed to investigate the effect of Er: YAG laser irradiation on debonding of cemented glass fiber posts in root canal treated teeth. Materials and Method: In this in vitro study, forty root canal treated mandibular premolar teeth were used in this study. Glass fiber posts were bonded using Panavia F 2.0 cement in the root canal space, and samples were divided into two groups. In the test group, samples were exposed to laser radiation of 7W, 350mJ, frequency of 20Hz and discontinued washing spray. In the control group, samples were left untouched. In each group, samples were sectioned into 1.5mm thick slices from the coronal, middle, and apical thirds of the root (N=120). Tensile bond strengths were evaluated using the push-out test and the failure patterns were evaluated using scanning electron microscopy (SEM). To compare the laser and non-laser groups at each location, independent sample t test was applied, and to compare bond strength between the locations in each group, one-way ANOVA and Tukey's HSD post hoc was applied. Results: A significant difference in tensile strength was observed between the laser-irradiated group and control group; tensile bond strength was much higher in the control group (p<0.001). The highest frequency of fractures was observed at the cement-dentin interface. Given the used parameters, complete debonding was not achieved in the laser-irradiated group. Conclusion: Laser radiation reduced the bond strength of glass fiber posts to resin cement without complete debonding.